Mobile Cloud Computing & Mobile Battery Augmentation Techniques: A Survey - Ali, Mushtaq; Jasni, Mohamad Zain; Mohamad Fadli, Zolkipli; Gran, Badshah (IEEE, 2014)
Energy efficiency of mobile devices is paramount after the tremendous advancement in technology while the explosion of smart mobile applications such as, YouTube, Facebook, Twitters and Google maps makes Smart Internet Devices (SIDs) the first choice of communication. On the other hand, multiple sensors and wireless interfaces drain battery swiftly, thus reducing the operational time of SIDs. Therefore, extending battery life problem has become of crucial research importance, at hardware and software levels, both alike. This paper firstly, makes contribution by reviewing different techniques at software level used to enhance battery life of SIDs in particular Smartphones. At the end, suggestions and opinions related to energy efficiency of SIDs are given, based on the comparative studies.